Diabetes-Induced Changes in Macrophage Biology Might Lead to Reduced Risk for Abdominal Aortic Aneurysm Development - Giulia Chinetti; Joseph Carboni; Joseph Murdaca; Claudine Moratal; Brigitte Sibille; Juliette Raffort; Fabien Lareyre; Elixène Jean Baptiste; Réda Hassen-Khodja; Jaap G. Neels (Metabolites, 2022)
Type 2 diabetes patients are less likely to develop an abdominal aortic aneurysm (AAA). Since macrophages play a crucial role in AAA development, we hypothesized that this decrease in AAA risk in diabetic patients might be due to diabetes-induced changes in macrophage biology. To test this hypothesis, we treated primary macrophages obtained from healthy human volunteers with serum from non-diabetic vs. diabetic AAA patients and observed differences in extracellular acidification and the expression of genes involved in glycolysis and lipid oxidation. These results suggest an increase in metabolism in macrophages treated with serum from diabetic AAA patients. Since serum samples used did not differ in glucose content, these changes are not likely to be caused by differences in glycemia. Macrophage functions have been shown to be linked to their metabolism. In line with this, our data suggest that this increase in macrophage metabolism is accompanied by a shift towards an anti-inflammatory state. Together, these results support a model where diabetes-induced changes in metabolism in macrophages might lead to a reduced risk for AAA development.